Pediatric stroke related to Lyme neuroborreliosis: Data from the Swiss NeuroPaediatric Stroke Registry and literature review. (January 2018) - Monteventi, O.; Steinlin, M.; Regényi, M.; Roulet-Perez, E.; Weber, P.; Fluss, J.
Abstract: Background: Cerebrovascular complications of Lyme neuroborreliosis (LNB) are poorly documented in the paediatric population. Methods: We performed a retrospective analysis from prospectively registered cases of acute ischemic stroke (AIS) from the Swiss NeuroPaediatric Stroke Registry (SNPSR) from 2000 to 2015. Only cases with serologically confirmed LNB were included. In addition, a literature review on paediatric stroke cases secondary to Lyme neuroborreliosis in the same time frame was performed. Results: 4 children out of 229 children with arterial ischemic childhood stroke and serologically confirmed LNB were identified in the SNPSR giving a global incidence of 1.7%. Median age was 9.9 years. A prior history of tick bites or erythema migrans (EM) was reported in two cases. Clinical presenting signs were suggestive of acute cerebellar/brainstem dysfunction. On imaging, three children demonstrated a stroke in the distribution of the posterior inferior cerebellar artery. The remaining fourth child had a "stroke-like" picture with scattered white matter lesions and a multifocal vasculitis with prominent basilar artery involvement. Lymphocytic pleocytosis as well as intrathecal synthesis of Borrelia burgdorferi antibodies were typical biological features. Acute intravenous third generation cephalosporins proved to be effective with rapid improvement in all patients. No child had recurrent stroke. Data from the literature concerning eight patients gave similar results, with prominent posterior circulation stroke, multifocal vasculitis and abnormal CSF as distinctive features. Conclusions: Lyme Neuroborreliosis accounts for a small proportion of paediatric stroke even in an endemic country. The strong predilection towards posterior cerebral circulation with clinical occurrence of brainstem signs associated with meningeal symptoms and CSF lymphocytosis are suggestive features that should rapidly point to the diagnosis. This can be confirmed by appropriate serological testing in the serum and CSF. Clinicians must be aware of this rare neurological complication of Lyme disease that demands specific antibiotic treatment. Highlights: Lyme neuroborreliosis (LNB) is a rare cause of pediatric stroke, even in endemic regions. Multifocal cerebral vasculitis, involving predominantly the posterior circulation, is a typical feature. CSF pleocytosis is a distinctive feature of LNB-related pediatric stroke. Diagnosis relies on intrathecal B. Burgdorferi antibodies production. Prompt antibiotic treatment is associated with good outcome.